SLIP OF THE TONGUE IN NEWS ANCHORS’ UTTERANCES ON INDONESIAN PRIVATE TV STATIONS (A CASE STUDY ON METRO TV AND TV ONE) - WIDYAWATI, LYA (Jurnal Ilmiah Mahasiswa FIB, 2013)
People need language to communicate with others during their life. In order to be understood by others, they are supposed to speak correctly. Yet, sometimes people cannot avoid a mistake, in this case is slip of the tongue (SOT). They produce utterances which are different from the concept that they have in their mind. Thus, in this study, the writer conducts a research about slip of the tongue found in news anchors’ utterances of Metro TV and TV One. There are two problems of the study, namely: (1) what are the types of slip of the tongue found in news anchors’ utterances at Indonesian private TV stations?; and (2) what are the possible factors influencing TV news anchor experiencing slip of the tongue?.            This research is a case study with qualitative approach. The data are the news anchors’ utterances of the news programs broadcasted on Metro TV and TV One. They were downloaded from Youtube from January 2013 to February 2013.            This research discloses that seven types of SOT (perseveration, anticipation, substitution, deletion, blend, exchange, misderivation) are found in the utterances that produced by the news anchors of Metro TV and TV One. The most dominant type of SOT found in this research is substitution. It occurs seven times and is found in several forms of substitution (noun, adverb, and preposition substitution). In further reading, there are various kinds of factors influencing the occurrence of SOT. The most dominant factors influencing Metro TV and TV One news anchors experiencing the SOT are internal and external difficulties which are proposed by Saksomo (2010). Those various conditions highly affect the news anchors’ performance in reporting the news.The writer suggests TV news anchors to be more aware and well prepared in their performance in order to minimize the occurrence of SOT. She also suggests to the next researchers to develop and explore this topic deeper in different object or theory. Keywords: slip of the tongue, Metro TV and TV One’s news anchors.